Principles and practice of clinical research - Gallin, John I. (Academic Press, 2002)
Principles and Practice of Clinical Research is a comprehensive text which addresses the theoretical and practical issues involved in conducting clinical research. This book is divided into three parts: ethical, regulatory, and legal issues; biostatistics and epidemiology; technology transfer, protocol development and funding. It is designed to fill a void in clinical research education and provides the necessary fundamentals for clinical investigators. It should be of particular benefit to all individuals engaged in clinical research, whether as physician or dental investigators, Ph. D. basic scientists, or members of the allied health professions, as well as both students and those actively participating in clinical research. Key Features * Comprehensive review ranging from a historical perspective to the current ethical, legal and social issues and an introduction to biostatistics and epidemiology * Practical guide to writing a protocol, getting funding for clinical research, preparing images for publication and display * Cohesive and clear presentation by authors carefully selected to teach a very popular course at NIH * Excellent companion text for courses on clinical research.